Sam Hill’s Adventures in Russia, 1899-1916: In His Own Words - Whisenhunt, Donald W.; Whisenhunt, William Benton (Journal of Russian American Studies, 2021)
This article explores the travel writings of Sam Hill, an American entrepreneur, during his three trips to Russia from 1899 to 1916. Hill’s observations, drawn from diaries, memoirs, articles, and letters, provide a unique perspective on Russian society, culture, and infrastructure in the late imperial era. His experiences, including encounters with Russian bureaucracy, pogroms, and social norms, reflect his outsider’s perspective shaped by American values. The authors argue that Hill’s narratives, housed in largely overlooked archives, offer significant historical insights into Russo-American relations, travel, and the cultural exchanges of the period